KEMAMPUAN LURAH PADA KOORDINASI PEMBANGUNAN DI KELURAHAN BANJER KECAMATAN TIKALA KOTA MANADO - AGUNE, DWI WAHYUNI; TULUSAN, FEMMY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: urban village head (Lurah) has the duty to execute the authority of the government that delegated bythe mayor to handle as a matter of regional autonomy, one of which is coordination. This research wasconducted with the aim of explaining the ability of urban village head on the coordination of development inKelurahan Banjer, Tikala Sub-district, Manado City. The research design used is qualitative. The researchfindings are the ability of the lurah to coordinate the development in Kelurahan Banjer, Tikala Sub-district,Manado City, in terms of technical capability in the administrative and technical processes work well verticallybut not horizontally. Humanity's ability is very prominent in the implementation of tasks, especially in guidingand directing the work of staff and to the community. Conceptual ability in the field of tasks in administrationand planning goes well.Keywords: Ability of urban village head, Coordination, Development.